Technology in the classroom: using graphics tablets for ESP lessons in agrarian and technical universities - Lemeshchenko-Lagoda, Viktoriia; Лемещенко-Лагода, Вікторія Володимирівна; Лемещенко-Лагода, Виктория Владимировна; Kurashkin, О. С.; Курашкін, О. С. (My University, 2019)
EN: The article is devoted to the aspects of using of graphics tablets on ESP lessons (English for specific purpose) by students of agrarian and technical specialties. The main prerequisites for the implementation of interactive teaching methods are determined, as well as the expediency of using information and communication technology (ICT) in order to prepare a competitive specialist that is able to use various language tools in a concrete communicative situation for the interaction among cultures. The necessity of developing new approaches to the organization of the educational process of learning English as a language for specific purpose, as well as its improvement and modernization, is considered. The importance of ICT implementation into the educational process and its significance for raising students’ learning and cognitive activity and motivation are highlighted and clarified. UK: Стаття присвячена питанням використання графічних планшетів на заняттях з іноземної мови професійного спрямування студентами немовних спеціальностей аграрного та технічного профілю навчання. Визначено головні передумови застосування інтерактивних методів навчання, а також обґрунтовано доцільність використання інформаційно-комунікаційних технологій з метою підготовки конкурентоспроможного спеціаліста, здатного використовувати різноманітні мовні засоби, необхідні у конкретній комунікативній ситуації для спілкування в умовах сьогодення. Обумовлено потребу розробки нових підходів щодо організації навчального процесу під час вивчення іноземної мови за професійним спрямуванням, а також його удосконалення та модернізації.
Технології аудиторного навчання: використання графічних планшетів на заняттях з англійської мови фахового спрямування в аграрних та технічних ЗВО
Keywords: interactive methods; graphics tablets; project technology; interactive approach; English for specific purposes (ESP); English as a foreign language (EFL); language competence; interaction skills; foreign language proficiency; інтерактивні методи навчання; графічні планшети; проектні технології; інтерактивний підхід; Англійська мова за професійним спрямуванням; Англійська як іноземна мова; мовна компетенція; навички взаємодії; рівень володіння іноземною мовою